Legal Analysis Of The Legal Relationship Between The Government, Railway Organizers, And The Public In Fulfilling The Safety Of Railway Level Crossing Users - Rendy Maulana; Ratu Mawar Kartina (Siber Nusantara Research, 2026)
The existence of unauthorized railway level crossings remains a significant issue in many regions of Indonesia. These crossings not only increase the risk of accidents but also raise complex legal questions regarding the legal relationship between the government, railway operators, and the public, particularly in determining liability when losses or damages occur. This study aims to examine the legal relationship among these parties in the use of unauthorized railway level crossings and to analyze civil liability arising from accidents based on Law Number 23 of 2007 on Railways and Article 1365 of the Indonesian Civil Code concerning unlawful acts. This research employs an empirical juridical method with a qualitative approach. Data were collected through a review of statutory regulations, legal literature, and relevant doctrines, supported by field observations and interviews with stakeholders involved in the management and use of railway crossings. The findings reveal that the legal relationship among the government, railway operators, and the public is inherently complex, as it encompasses both public and private law dimensions. The government is responsible for regulation, supervision, and infrastructure provision, while railway operators are obliged to ensure the safety of railway operations. Meanwhile, the public is required to comply with applicable laws and safety regulations. The study further demonstrates that civil liability for accidents occurring at unauthorized railway crossings should not be imposed solely on one party. Instead, liability must be determined by considering the degree of fault, the causal relationship between the act and the resulting damage, and the respective roles of each party. A proportional allocation of liability provides a more equitable approach to ensuring legal certainty, justice, and legal protection for all parties involved.